A Study on the Effectiveness of College English Teaching Based on Content-Based Instruction Teaching Philosophy - Zhang, Lu; Li, Qian; Liu, Wei (Frontiers in Psychology, 2022)
With the rapid development of international economy and trade, English talents have become the focus of social attention. Therefore, the innovation and research of College English teaching has become a hot spot in the field of education. Relevant research results are also constantly updated, but there are no ideas and methods that can adapt to the actual teaching. In order to improve students' English level and cultivate excellent English talents for the development of the country, this study constructs and implements the College English teaching model based on CBI teaching concept from an empirical perspective. In the teaching, it focuses on the theme content that students are interested in. Teachers take explaining the theme content as a means, use content teaching to drive language teaching and realize the purpose of language teaching. The experimental class adopts CBI teaching concept, the blank class adopts ordinary teaching methods, and the control class adopts task-based teaching concept. Through one semester of teaching, the teaching effect of three classes is evaluated. Under the evaluation of teachers, the full score of CBI teaching effectiveness is 66. Under the evaluation of students, the full score of CBI teaching effectiveness is 64, which is the highest. This shows that the effectiveness of be teaching under CBI is higher than task-based teaching and general teaching. The results showed that the average score of the pre-test control class was the highest, the average score of the middle test experimental class was the highest, an increase of 4.7 points, and the average score of the post test experimental class was the highest, an increase of 112.2 points, while the scores of the control group and the blank group were 108.7 points and 104.3 points respectively. This shows that the learning effect of CBI teaching concept is higher than task-based teaching and general teaching. Therefore, college English teaching based on CBI teaching concept has high effect, can improve students' English knowledge and ability, and can be promoted in college English teaching.